2021
DOI: 10.1177/1049909120987215
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Services in the NeuroICU: Opportunities and Persisting Barriers

Abstract: Background: End-of-life (EOL) supportive care, including palliative and hospice services, is an area of increasing importance in critical care. Neurointensivists face unique challenges in providing timely supportive care to terminally ill patients expected to expire in the NeuroICU. Objective: This study explored the extent of effective utilization of, and recorded barriers to, palliative and hospice services in a dedicated 30-bed NeuroICU at a large academic medical center. Design: A retrospective chart revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…From a total of 915 records retrieved, after duplicate exclusion and screening from abstracts, 363 relevant articles were screened from full text; of those, 15 articles [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] were adjudicated relevant for inclusion in this review and provided the basis for data and discussion presented on the topic ( Table 1 ). Twelve studies were conducted in a single center, and only three were multicentric studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a total of 915 records retrieved, after duplicate exclusion and screening from abstracts, 363 relevant articles were screened from full text; of those, 15 articles [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] were adjudicated relevant for inclusion in this review and provided the basis for data and discussion presented on the topic ( Table 1 ). Twelve studies were conducted in a single center, and only three were multicentric studies.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, palliative care needs in patients admitted to neuro-ICUs are often unmet or met late. A retrospective study based on a chart review of patients who died in neuro-ICU found that 44% of expired patients never received palliative care referral, and that patients were, on average, referred only 1 day before death [ 8 ]. On the other hand, evidence exists for a high prevalence of palliative care needs in a neuro-ICU (62%), which may be detected if systematically screened [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goals of care discussions and treatment decisions were the overwhelming reason for palliative care involvement 124 . A lack of referrals and delays in referral impede patient access to palliative care, 125 so inclusion of this team in the care of patients with stroke due to LVO should be considered as appropriate.…”
Section: Family Communication and Neuropalliative Care After Stroke D...mentioning
confidence: 99%
“…They also can have difficulties engaging family members in evidence- and value-informed decision-making due to the physical, psychological, and cognitive (e.g., difficulties synthesizing vast amounts of information) challenges of having a family member in the ICU; any history of personal or family conflicts; or previous experiences with healthcare systems ( 16 ). Additional, consultations often are not sought at all or in a timely fashion or are unavailable due to resource constraints ( 24 ).…”
Section: Family-centered Carementioning
confidence: 99%